Designing and evaluating online communities for promoting self-management of chronic low back pain. (3rd January 2008) - Rubinelli, Sara; Schulz, Peter J.; Vago, Fausto
This study discusses the organisation of a virtual community composed of health professionals and patients affected by chronic low back pain. The community was created as part of a pilot study for promoting self-management of the disease. The article deals with the social and theoretical framework behind the development of the community, as well as with the way health professionals and patients interact on a website specifically designed for the project. A discussion on the evaluation of the results completes the enlightenment of crucial factors for further applications in the field.